KOMITMEN DAN MOTIVASI KERJA DALAM MENINGKATKAN KINERJA GURU - Marlina Marlina; Aliman Aliman; Manap Somantri (Manajer Pendididikan, 2018)
Abstract : The purpose of the research is to describe how commitment and teacers work motivation in increasing teachers work performance seein from their job’s implementation and in an effort to improve the quality of study result at SMAN 6 Bengkulu. The research method which is used is descriptive qualitative research methtode. The subject of this research is school principal and teachers at SMAN 6 Bengkulu. To collect the  data, the researcher used observation, interview, and documentation. The result of the research showed that commitment and motivation of teachers performance at SMAN 6 Bengkulu is there were significant appropriateness standard of the techers work perpormance we see it from the attendance, teachers act in doing their job and cooperation in increasing the quality of study result at SMAN 6 Bengkulu. Keyword : commitment, work motivation, teachers performance